2015
DOI: 10.1371/journal.pone.0141741
|View full text |Cite
|
Sign up to set email alerts
|

Virological Characteristics of Acute Hepatitis B in Eastern India: Critical Differences with Chronic Infection

Abstract: Hepatitis B Virus (HBV) manifests high genetic variability and is classifiable into ten genotypes (A-J). HBV infection can lead to variable clinical outcomes, ranging from self-limiting acute hepatitis to active chronic hepatitis, cirrhosis and hepatocellular carcinoma. The present study characterizes HBV strains circulating among patients with acute (AHB) and chronic HBV infection (CHB). Among a total of 653 HBsAg positive cases, 40 manifested acute infection. After sequencing the surface(S), basal core promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Assuming that the main findings in Huh7 cells can be extrapolated to in vivo HBV infection, the variations in overall replication capacity of D-subgenotypes may underlie some of the key differences in clinical features associated with these subgenotypes. It had been reported that HBV/D2 was the major circulating D-subgenotype in patients with acute HBV infection in eastern India 35 as well as in Japan 36 and its enhanced replication capacity correlated with high viremia titers and elevated ALT levels in these patients. In contrast, D5 was conspicuously absent in the acute hepatitis B patients 35 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Assuming that the main findings in Huh7 cells can be extrapolated to in vivo HBV infection, the variations in overall replication capacity of D-subgenotypes may underlie some of the key differences in clinical features associated with these subgenotypes. It had been reported that HBV/D2 was the major circulating D-subgenotype in patients with acute HBV infection in eastern India 35 as well as in Japan 36 and its enhanced replication capacity correlated with high viremia titers and elevated ALT levels in these patients. In contrast, D5 was conspicuously absent in the acute hepatitis B patients 35 .…”
Section: Discussionmentioning
confidence: 92%
“…It had been reported that HBV/D2 was the major circulating D-subgenotype in patients with acute HBV infection in eastern India 35 as well as in Japan 36 and its enhanced replication capacity correlated with high viremia titers and elevated ALT levels in these patients. In contrast, D5 was conspicuously absent in the acute hepatitis B patients 35 . However, among the chronically HBV/D infected patients, the viral load had been found to be highest in patients carrying HBV/D1 37 .…”
Section: Discussionmentioning
confidence: 92%
“…For instance, the peak ALT levels in acute hepatitis B with genotype A (2,137±1,088 U/L) are significantly lower than those with genotypes B (3,078±2,111 U/L) or C (2,624±1,843 U/L) ( 3 ). In a study from India, the peak ALT value in acute hepatitis B caused by genotype D tended to be lower than that caused by genotype C ( 9 ). In contrast, the peak ALT level in Ehime Prefecture with genotype D was 2,236±2,202 U/L, which was higher than that with genotype A (1,425±630 U/L) ( 4 ).…”
Section: Discussionmentioning
confidence: 88%
“…An indirect confirmation of our assumption is the work that showed the prevalence of HBV D2 and D3 in patients who recognized risky sexual behavior, while a group of patients who claimed to have been infected by surgery or blood transfusion shown many subgenotypes. This may be due to the fact that patients who underwent surgery and blood transfusion were exposed to several sources of infection [40].…”
Section: Resultsmentioning
confidence: 99%